A formação inicial de professores de Física e os saberes docentes para a prática educativa: revisão de escopo de 2001 a 2022 - Cyrineu, Ana Amélia Cyrineu Plens (2023)
Teaching is a profession full of challenges, especially at the beginning of the career in which there are aspects linked to lesson planning, class management, working conditions, among other particularities, which, although they are addressed during initial training, the situations that emerge from daily work at school, presenting situations that require the mobilization of different knowledge from the teacher. This understanding leveraged the development of this research, whose objective is to map the field related to research on the initial training of Physics teachers, aiming to understand how the knowledge mobilized by the teacher in the classroom has been approached in research such as dissertations, theses, and how they are presented within the scope of the guidelines for the initial training of Physics teachers. To this end, we defined the following specific objectives: 1) Identify and analyze the works found in the CAPES Catalog of Theses and Dissertations related to the knowledge of Physics teachers in Basic Education; and 2) Identify the knowledge in the regulations related to the initial training of Physics teachers. To develop the research, a scoping review was carried out, covering the years 2001 to 2022, in which the analyzes were carried out based on the assumptions of Tardif (2012) and from this, the following axes emerged: Knowledge from the profession; Knowledge arising from professional training for teaching and Knowledge in regulations relating to teacher training. Based on the data analyzed, we identified that knowledge from experience is essential for teacher training, there are indications that supervised internships provide possibilities for future teachers to come into contact with school culture, as well as aspects inherent to the work teacher. In this direction, we highlight the emphasis on articulation between teacher training institutions and basic education schools, which can provide greater approximation with the future teacher's work reality, with the support of professionals involved in teacher training.